Toward Rational Understandings of α-C–H Functionalization: Energetic Studies of Representative Tertiary Amines - Luo, Wenzhi; Yang, Jin-Dong; Cheng, Jin-Pei (iScience, 2020)
Functionalization of α-C–H bonds of tertiary amines to build various α-C–X bonds has become a mainstream in synthetic chemistry nowadays. However, due to lack of fundamental knowledge on α-C–H bond strength as an energetic guideline, rational exploration of new synthetic methodologies remains a far-reaching anticipation. Herein, we report a unique hydricity-based approach to establish the first integrated energetic scale covering both the homolytic and heterolytic energies of α-C–H bonds for 45 representative tertiary amines and their radical cations. As showcased from the studies on tetrahydroisoquinolines (THIQs) by virtue of their thermodynamic criteria, the feasibility and mechanisms of THIQ oxidation were deduced, which, indeed, were found to correspond well with experimental observations. This integrated scale provides a good example to relate bond energetics with mechanisms and thermodynamic reactivity of amine α-C–H functionalization and hence, may be referenced for analyzing similar structure-property problems for various substrates. [Display omitted] •A unique hydricity-based methodology for bond energy determination•The first integrated α-C–H bond energy scale of tertiary amines•Thermodynamics-based diagnosis of the feasibility/mechanism of amine oxidation Organic Chemistry; Organic Synthesis; Physical Organic Chemistry